2018
DOI: 10.1148/radiol.2017170044
|View full text |Cite
|
Sign up to set email alerts
|

Subsolid Lung Nodule Classification: A CT Criterion for Improving Interobserver Agreement

Abstract: Purpose To evaluate an objective computed tomographic (CT) criterion for distinguishing between part-solid (PS) and nonsolid (NS) lung nodules. Materials and Methods This study received institutional review board approval, and patients gave informed consent. Preoperative CT studies in all patients who underwent surgery for subsolid nodules between 2008 and 2015 were first reviewed by two senior radiologists, who subjectively classified the nodules as PS or NS. A second reading performed 1 month later used pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…Although radiologists are able to assess the invasive probability of PSNs using semantic or morphologic CT features (eg, diameter, solid proportion) and medical history in clinical practice, this method is limited by subjectivity and creates a work burden (10)(11)(12). Automated volumetric analysis facilitates the quantification of the nodule volume and mean density with higher repeatability than manual measurement (13).…”
Section: Key Resultsmentioning
confidence: 99%
“…Although radiologists are able to assess the invasive probability of PSNs using semantic or morphologic CT features (eg, diameter, solid proportion) and medical history in clinical practice, this method is limited by subjectivity and creates a work burden (10)(11)(12). Automated volumetric analysis facilitates the quantification of the nodule volume and mean density with higher repeatability than manual measurement (13).…”
Section: Key Resultsmentioning
confidence: 99%
“…The correlations between pathological findings and thinsection CT features of SSNs have been evaluated in numerous studies and have provided new opportunities for predicting the histologic subtype of adenocarcinoma (22). The qualitative/ semiquantative/quantative measurements have been applied to distinguish preinvasive and invasive lesions (22À27).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Such overdiagnosis and overtreatment are especially seen in slow-growing lung adenocarcinomas that are mostly represented by subsolid nodules (SSNs). [6][7][8][9][10] Retrospective studies assessing precursor lesions of interval cancers and post-screen cancers showed that SSNs were visible at the tumor sites years before tumor diagnosis. 11 Such retrospective evidence prompted more conservative algorithms in the most recent guidelines.…”
Section: Introductionmentioning
confidence: 99%